2021
DOI: 10.1007/s12237-020-00877-z
|View full text |Cite
|
Sign up to set email alerts
|

How Do Geological Structure and Biological Diversity Relate? Benthic Communities in Boulder Fields of the Southwestern Baltic Sea

Abstract: Environmental factors shape the structure and functioning of benthic communities. In coastal zones of the southwestern Baltic Sea, boulder fields represent one of the most productive habitats, supporting diverse benthic communities that provide many ecosystem services. In this study, the influence of the geological characteristics of boulder fields on the biodiversity of associated hard-bottom communities was investigated at two different spatial scales (few kilometers and tens of kilometers). The analyses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
(69 reference statements)
2
11
0
Order By: Relevance
“…Recent studies, including the present investigation, demonstrated that stone size is a fundamental driver of SNHS epibenthic (epilithic) species assemblages [24,25]. Furthermore, besides the size of individual stones, seascape patterns, such as the striations and elliptical shapes herein identified, can be important proxies of biological communities (describing the relation between geological and biological structure, e.g., [83,84]. Therefore, at such scales, the integration of MBES and UI by RF for regression largely improves the identification of the ecology of such seascape patterns.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Recent studies, including the present investigation, demonstrated that stone size is a fundamental driver of SNHS epibenthic (epilithic) species assemblages [24,25]. Furthermore, besides the size of individual stones, seascape patterns, such as the striations and elliptical shapes herein identified, can be important proxies of biological communities (describing the relation between geological and biological structure, e.g., [83,84]. Therefore, at such scales, the integration of MBES and UI by RF for regression largely improves the identification of the ecology of such seascape patterns.…”
Section: Discussionsupporting
confidence: 52%
“…Hitherto, only a few cases have been published showing the importance of geological complexity or geodiversity in marine management, e.g., [84,85], but clearly if these coincide with hotspots of biodiversity, a new era is emerging in the mapping of SNHS. This is indeed the case for the Southern North Sea region, having a complex geological history and a diverse morphosedimentary setting.…”
Section: Discussionmentioning
confidence: 99%
“…Within Placentia Bay, boulder and gravel fields occur along the offshore extent of D'Argent Bay and Burin and along the shoreline of Rushoon and St. Lawrence. These fields may provide a level of stability and topographical diversity that could increase structural availability for sessile invertebrates (MacArthur and Wilson, 1967;Liversage and Chapman, 2018;Franz et al, 2021), such as the sponges and anemones observed in Rushoon and St. Lawrence. These areas were found to be associated with a higher presence of arcto-boreal species, such as the different morphotypes of porifera and anthozoan as well as species of echinoderms and crustaceans.…”
Section: Discussionmentioning
confidence: 99%
“…Especially filter-feeding organisms are known to be sensitive against sedimentation effects since their feeding apparatus can be clogged [74,75]. Therefore, it appears likely that these disturbance-related effects were responsible for the observed differences in community structure [76].…”
Section: Benthic Community Structurementioning
confidence: 99%